Pengaruh Environmental Concern terhadap Intensi Menggunakan Bus Trans Metro Pasundan pada Masyarakat Kota Bandung - Anisa Cantika Umbara Putri; Milda Yanuvianti (UNISBA Press, 2023)
Abstract. The problem of air pollution is one of several environmental issues that are still frequently experienced. In terms of pollution, Bandung is the third most polluted city in Indonesia. The government introduced the newest public transportation in an effort to lower it, the Trans Metro Pasundan Bus, which is supported by the Friends Bus app. Therefore, it is still possible to research the elements that most influence people's propensity to pick bus transportation. One of the theories that can explain the elements that can affect a person's intention to utilize the Trans Metro Pasundan Bus is the Theory of Planned Behavior. Additionally, the influence of environmental concerns on people's decisions to take the Trans Metro Pasundan Bus will be investigated. In this study, 230 Bandung city residents between the ages of 18 and 40 participated as respondents. The Intention to Use Carsharing Scale from Zhang and Li was the measuring instrument employed in this study. To determine the factors that are important in persuading people to use the Trans Metro Pasundan Bus, structural equation modeling (SEM) is the data analysis method used. The findings revealed that individual intentions to ride the Pasundan Trans Metro Bus were significantly influenced by attitude toward conduct and subjective norms. Individuals' intentions to use the services, however, are not significantly impacted by perceived behavioral control and environmental concern. This study suggests to strengthen the promotion regarding the use of bus public transportation by related government agencies. Abstrak. Masalah lingkungan adalah masalah yang masih sangat sering ditemui, salah satunya masalah polusi udara. Kota Bandung berada pada peringkat ketiga sebagai kota paling berpolusi di Indonesia. Dalam upaya untuk menguranginya, pemerintah meluncurkan transportasi umum terbaru yaitu Bus Trans Metro Pasundan yang didukung oleh aplikasi Teman Bus. Karena itu, kecenderungan masyarakat untuk memilih moda transportasi bus tersebut masih dapat diteliti mengenai faktor apa yang paling berperan. Theory of Planned Behavior menjadi salah satu teori yang dapat menjelaskan faktor-faktor yang dapat mempengaruhi intensi individu dalam menggunakan Bus Trans Metro Pasundan. Selain itu, faktor kepedulian lingkungan juga akan diteliti untuk mengetahui apakah hal tersebut juga memengaruhi individu dalam memilih Bus Trans Metro Pasundan. Penelitian ini melibatkan 230 responden yang berusia 18 - 40 tahun yang berdomisili di Kota Bandung. Alat ukur yang digunakan pada penelitian ini adalah skala Intention to Use Carsharing dari Zhang dan Li. Analisis data yang digunakan adalah structural equation modelling (SEM)untuk menemukan faktor yang signifikan dalam mempengaruhi individu untuk menggunakan Bus Trans Metro Pasundan. Hasil penelitian menunjukkan bahwa attitude toward behavior dan subjective norms memiliki pengaruh yang signifikan terhadap intensi individu untuk menggunakan Bus Trans Metro Pasundan. Sedangkan perceived behavioral control dan environmental concern tidak berpengaruh signifikan terhadap intensi individu untuk menggunakan Bus Trans Metro Pasundan.